RECOVERY EMOTIONS ON PERCEIVED JUSTICE - Yolanda Masnita; Sri Vandayuli Riorini (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2018)
Recovery service failures can affect a greater failure if not handled properly. The purpose of this study was to examine the effect of pre-recovery emotions and post-recovery in services. Data were collected using a questionnaire distributed to 216 respondents who have used the services retail market and then experienced a service failure followed by a recovery service. In this study, positive and negative emotions post-recovery are the dependent variables, while the severity of service failure, the pre-recovery emotions and perceived fairness other variables major variable. In line with this goal, eight hypotheses were tested using structural equation modeling analysis with the aim to clarify the relationships between variables. The results show that the post-recovery of positive or negative emotions are influenced by the severity of the failure of the service, but the effect is mediated by the second pre-recovery emotions. Meanwhile, there is no mediating effect of perceived justice on the emotions of pre-recovery and post-recovery. This study implies that, during recovery services, service providers must simultaneously consider the positive and negative emotions. In addition, managers should also consider the depth of the severity of service failure to determine the pre-recovery emotions. Selection of the type of recovery will have an impact on the perceived fairness, so that providers have to respond better to emotional recovery.